Successful heart transplantation in an infant with phosphoglucomutase 1 deficiency (PGM1‐CDG). Issue 2 (22nd November 2022) - Altassan, Ruqaiah; Albert‐Brotons, Dimpna C.; Alowain, Mohammad; Al‐Halees, Zohair; Jaeken, Jaak; Morava, Eva
Abstract: We report successful heart transplantation in a phosphoglucomutase 1 deficient (PGM1‐CDG) patient. She presented with facial dysmorphism, bifid uvula and structural heart defects. Newborn screening was positive for classic galactosemia. The patient was on a galactose‐free diet for 8 months. Eventually, whole exome sequencing excluded the galactosemia and revealed PGM1‐CDG. Oral D‐galactose therapy was started. Rapid deterioration of the progressive dilated cardiomyopathy prompted heart transplantation at the age of 12 months. Cardiac function was stable in the first 18 months of follow‐up, and hematologic, hepatic, and endocrine laboratory findings improved during D‐galactose therapy. The latter therapy improves several systemic symptoms and biochemical abnormalities in PGM1‐CDG but does not correct the heart failure related to cardiomyopathy. Heart transplantation has so far only been described in DOLK‐CDG.